Methodology to Promote Physical Activity Monitoring Adherence in Youth with Autism Spectrum Disorder - Hauck, Janet L.; Ketcheson, Leah R.; Ulrich, Dale A. (Frontiers in Public Health, 2016)
Background: Objective physical activity (PA) monitoring via accelerometry is both costly and time consuming. Furthermore, overall adherence to a monitoring protocol is often complicated by disability. Therefore it is essential that strategies for supporting accelerometer wear for youth with disabilities are maximized. The purpose of this perspective was to provide researchers a set of efficacious PA monitoring strategies based on the retrospective examination of support methodology on adherence rates for youth with Autism Spectrum Disorder (ASD). Method: Accelerometer data was collected for 163 participants with ASD in three independent cohorts. Each cohort was provided a varying set of support strategies to help maximize adherence. Chi-square analysis was used to determine differences in adherence between each cohort. Results: Adherence rates significantly increased from 51.9% in cohort 1 to 88.7% in cohort 2 [X2(1) =18.333, p<0.001] and again from 88.7% in cohort 2 to 97.4% in cohort 3 [X2(1) =2.663, p=0.103]. The greatest increase in adherence was observed from 51.9% in cohort 1 to 97.4% in cohort 3 [X2(1) =19.837, p<0.001]. Support strategies associated with these increases included: 1) social story; 2) incentive; 3) concealing techniques; and 4) 24 hrs/day wear instructions. Conclusions: Adherence to PA measurement increased when additional support strategies were utilized in combination with a traditional protocol. We recommend these support methodology be considered as preliminary best-practices when measuring objective PA in youth with ASD with likely success in other disability populations.